microRNA regulation of smooth muscle gene expression and phenotype - Kang, Hara (Curr Opin Hematol, 2012)
PURPOSE OF REVIEW: In this review, we summarize recent advances regarding microRNA (miRNA) functions in the regulation of vascular smooth muscle cell (VSMC) differentiation and phenotypic modulation. RECENT FINDINGS: Multiple miRNAs are found to be responsible for VSMC differentiation and proliferation under physiological or pathological condition. A single miRNA downregulates multiple targets, whereas a single gene is regulated by multiple miRNAs to modulate a specific aspect of VSMC phenotype. SUMMARY: The phenotype of VSMCs is dynamically regulated in response to environmental stimuli. Deregulation of phenotype switching is associated with vascular diseases. Several miRNAs have been found to be highly expressed in the vasculature, to modulate VSMC phenotype, and to be dysregulated in vascular diseases. By regulating mRNA and/or protein levels post-transcriptionally, miRNAs provide a delicate regulation in the complex molecular networks that regulate the vascular system. Understanding the functions of miRNAs in the regulation of VSMC differentiation and phenotype switching provides new insights to the mechanisms of vascular development, function, and dysfunction.